PENGARUH GENDER SEBAGAI PEMODERASI PADA HUBUNGAN ORIENTASI PASAR DAN KINERJA KEUANGAN - Maria Pampa Kumalaningrum (Jurnal Riset Akuntansi dan Keuangan, 2010)
This study examined the effect of gender as moderating variable on relationship  between market orientation and financial performance. Market orientation reflects the  degree to which firms’ strategic market planning is driven by customer and competitor  intelligence. Data was analyzed using Chow analysis. The results showed that market  orientation has an effect on financial performance either in female or male–owned  micro business. The study also shown that gender had moderating effect on relationship between market orientation and financial performance. Keywords: gender, market orientation, and financial performance.